Gastroesophageal reflux disease and the relationship with Helicobacter pylori - Mungan, Zeynel; Pınarbaşı Şimşek, Binnur (Turkish Journal of Gastroenterology, 2017)
Abstract After Helicobacter pylori was identified, and its relationship with peptic ulcer disease was exactly shown, the relationship of this bacterium with gastroesophageal reflux disease (GERD) gained momentum and discussions continue to this day. We reviewed the literature for the relationship between H. pylori and GERD. According to the existing data, there is no relationship between GERD and H. pylori presence. Successful eradication therapy does not have an impact on the emergence or exacerbation of GERD. However Barrett's esophagus and esophageal adenocarcinoma are less frequent, especially in the presence of CagA positive H. pylori infections. Long-term use of proton pump inhibitor (PPI) may have an impact on the development of atrophy and/or intestinal metaplasia in H. pylori positive patients; therefore, H. pylori eradication is recommended in patients that should use long-term PPI. As a conclusion, H. pylori screening and the eradication decision should be independent of GERD, except for patients that will use long-term PPI. Cite this article as: Mungan Z, Pınarbaşı Şimşek B. Gastroesophageal reflux disease and the relationship with Helicobacter pylori. Turk J Gastroenterol 2017;28(Suppl 1); S61-S67 Full Text Turkish